PROSPECTS FOR STRENGTHENING PARTNERSHIPS BETWEEN THE PUBLIC AND PRIVATE SECTORS IN SUPPORTING SMALL BUSINESSES - Ibrokhimov, Mukhammadzhon Abdullajanovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the importance of public-private partnerships in small business development, economic efficiency, and prospects. The study examines the role of public-private partnership mechanisms in supporting small businesses. The results show that strengthening partnerships increases investment, creates new jobs, and ensures economic stability.